A framework for preventing illegitimate e-prescribing practices - Kim, Deuk Hun; Kwak, Jin (Lecture Notes in Electrical Engineering, 2018)
The e-prescribing system was introduced to improve convenience for patients when they use healthcare services. However, security is still a critical aspect because illegitimate e-prescribing systems can lead to serious problems. This paper aimed to propose a framework for preventing illegal issuance e-prescribing practices by applying case-by-case approaches and a cloud-based national prescription database.
Keywords: Cloud-based; Healthcare services; Illegal issuance prevention; Medical security; E-prescribing system; Illegal issuance prevention; Medical security